Exercise capacity in ventricular assist device patients: clinical relevance of pump speed and power†. (12th May 2016) - Fresiello, Libera; Buys, Roselien; Timmermans, Philippe; Vandersmissen, Katrien; Jacobs, Steven; Droogne, Walter; Ferrari, Gianfranco; Rega, Filip; Meyns, Bart
Abstract: OBJECTIVES: Patients with ventricular assist device (VAD) show a limited exercise capacity. The aim of this work is to investigate whether VAD speed increase has an effect on exercise performance in the upright position. METHODS: Fourteen patients implanted with a HeartMate II underwent two cardiopulmonary maximal exercise tests on an upright bicycle ergometer the same day. During one test, VAD speed was set as constant (CONST) and during the other test, VAD speed was increased by 200 rpm each minute (INCR). RESULTS: No statistical differences were found between the two tests in terms of maximum heart rate, peak oxygen uptake, peak minute ventilation, ventilation efficiency slope and arterial blood pressure. Patients' fatigue perception, measured with a Borg scale, was similar between the two tests over the entire group (15 ± 1 for both CONST and INCR). VAD flow increased from 4.5 ± 0.7 to 6.0 ± 1.0 l/min during CONST and to 7.6 ± 1.4 l/min during INCR. Four patients experienced an easier cycling during INCR, and the other patients noticed no difference. One patient had a suction event during INCR and another had non-sustained ventricular tachycardia at peak exercise. A negative correlation was found between the rate of increase in VAD power during exercise and peak oxygen uptake. CONCLUSIONS: Although VAD speed increase provided an additional pump flow of 1.6 l/min at peak exercise, no significant objective and subjective benefits on patients' exercise performance were observed. Finally, VAD power could be a useful parameter to monitor patients during exercise.